2019
DOI: 10.3389/fpsyg.2019.02405
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement and Cognitive Development in Early and Middle Childhood: A Systematic Review

Abstract: This systematic review aims to examine the existing literature concerning the association between father involvement and the development children's cognitive skills during early and middle childhood. Specifically, it analyzes: (1) how the number of researches developed across years; (2) which are the main socio-demographic characteristics of the samples; (3) which are the main focuses examined; and (4) which operational definitions were used to assess father involvement and children cognitive skills. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 83 publications
2
63
0
7
Order By: Relevance
“…However, parents may adjust to their children’s characteristics. When a parents is are not able to adjust to their infant’s needs due to mental health and personal and contextual strains, their offspring may be at risk for developmental perturbations like behavioral and cognitive difficulties ( Rollè et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, parents may adjust to their children’s characteristics. When a parents is are not able to adjust to their infant’s needs due to mental health and personal and contextual strains, their offspring may be at risk for developmental perturbations like behavioral and cognitive difficulties ( Rollè et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive involvement of fathers can impact not only children’s cognitive skills but also their social competences and behavioural or emotional outcomes. 38–40 This shows, together with fathers’ important role as decision-maker and breadwinner in the care-seeking process, that there is a strong need for including fathers in future interventions aimed at improving maternal and child health. It is thereby crucial to consider that many fathers spend much of their time away from home because of their work.…”
Section: Discussionmentioning
confidence: 99%
“…We found father's education as the second predictor for the socioeconomic status latent variable and directly related to infant cognitive skills, similar to previous studies. 33,34 As an example, Cabrera et al 34 showed that a father's formal education, beyond high school, positively affects infant performance in the cognitive subscale of Bayley when they are 3 years old. Here we provided similar evidence 2 years earlier in the infant lifespan, supporting earlier referral to targeted intervention.…”
Section: Cognitive Developmentmentioning
confidence: 99%
“…A few studies have investigated the father's role, [33][34][35] mainly describing how parents' responsibilities have changed over the last decades and underlining that the presence of the father in infants care should not be overlooked. 36 Father's involvement should be examined beyond providing financial resources for the child's development.…”
Section: Cognitive Developmentmentioning
confidence: 99%